Differentiation between IgG4-related Mikulicz disease and Sjögren's syndrome: A review case report and literature review. Issue 52 (30th December 2022) - Otani, Yurie; Shimura, Tomotaka; Nogaki, Taketoshi; Ikenoya, Yoichi; Oyake, Koichiro; Imaizumi, Naomi; Inoue, Yukiko; Uruma, Shuhei; Kamimura, Sawa; Kawamura, Yojiro; Kobayashi, Sei
Abstract : Rationale: IgG4-related diseases cause lesions in various organs throughout the body. In otorhinolaryngology, IgG4-related Mikulicz's disease is suspected and diagnosed based on the presence of lesions of the head and neck, salivary and lacrimal gland enlargement, and bilateral sinus opacity concentrated on the maxillary sinuses. However, in some cases, it is necessary to consider about differentiation between IgG4-related Mikulicz's disease and Sjögren syndrome. Patient concerns and diagnosis: A 75-years-old male patient visited our hospital with bilateral otitis media with effusion, which was resistant to conservative treatment. Other symptoms at presentation included enlarged bilateral submandibular and sublingual glands marked oral dryness, severe decrease in saliva secretion (1 mL/10 minutes), and dry eyes. We conducted a Schirmer's and fluorescent dye tests, both of which were positive. High serum IgG4 levels were observed, and although the Sjögren syndrome (SS)-A/SS-B antibodies were negative, marked hypolacrimation and tear secretion were observed. Therefore, a detailed examination considering both IgG4-related Mikulicz's disease and SS was conducted. Salivary gland scintigraphy performed prior to the salivary gland biopsy revealed a marked decrease in uptake, which satisfied the diagnostic criteria for SS; however, it was difficult to diagnose IgG4-related disease based on the diagnostic definition. Intervensions: Although a definitive diagnosis of SS was made, the persistent otitis media with effusion that was resistant to conservative treatment and bilateral mixed hearing loss were confirmed. As mixed hearing loss is considered an otological symptom of IgG4-related disease, oral steroid treatment was administered. Outcome: Thereafter, marked recovery of hearing and reduced swelling and induration of the bilateral parotid and submandibular glands were observed. Clinically, IgG4-related Mikulicz's disease was strongly suspected, but a definite diagnosis of SS was made. lessons: In the absence of an IgG4-related Mikulicz's disease diagnosis, careful differentiation between IgG4-related Mikulicz's disease and 2 diseases and their diagnostic criteria was essential.